Peran KUA Medan Polonia dalam Menyikapi Pernikahan di Bawah Umur - Amir, Sulaiman Muhammad; Armayani, Ela; Sunita, Sunita; Khirani, Lili; Saragih, Cita Rahma; Naamudin, Naamudin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The phenomenon of underage marriage is often found in Indonesian society and raises serious problems, Indonesia is ranked second in Southeast Asia. In mid-2019 the BKKBN also released that as many as 375 teenagers in Indonesia were married underage, therefore the importance of the role of KUA in addressing this problem. Method: This type of research uses descriptive qualitative with an empirical approach. The research was conducted in November 2022 at the KUA Medan Polonia. The data used used primary data collected through interviews and observation as well as secondary data. Data management and analysis techniques were carried out in three stages, namely data reduction, data presentation and conclusion. Results: The implementation of marriages that have so far occurred at the Medan Polonia KUA, if a partner is found who is underage, it is mandatory to attach a letter of dispensation obtained through the religious court. Conclusion: Responding to the problem of underage marriages KUA Medan Polonia made several efforts to overcome this problem starting from checking files, optimizing the role of BP4, as well as conducting counseling and socialization of the Marriage Constitution.